The Effects of Breviscapine Injection on Hypertension in Hypertension-Induced Renal Damage Patients: A Systematic Review and a Meta-Analysis - Wu, Lihua; Gao, Yanhua; Zhang, Shufei; Fang, Zhuyuan (Frontiers in Pharmacology, 2019)
Background: Breviscapine (Dengzhanhua) injection has been wildly used in clinical treatment for cerebral infarction, cardiovascular disease, diabetic nephropathy, renal impairment of essential hypertension and stroke in China. Breviscapine injection and antihypertensive drugs combination therapy is supposed to be beneficial for hypertension-induced renal damage patients. Objectives: To evaluate the beneficial and adverse effects of breviscapine injection on hypertension in hypertension-induced renal damage patients, an extensive meta-analysis was performed. Methods: We searched PubMed, the Cochrane Library, Embase, CNKI, Sino Med, VIP, and Wanfang Data for relevant literature. The timeframe of retrieval was set from the founding date of each database to September 28, 2018. Results: Fourteen papers were included in this study. The quality of all the studies included was determined to be low. All studies were conducted with Chinese populations. Meta-analysis showed that, compared with single-use antihypertensive drugs, using breviscapine injection in combination with antihypertensive drugs to treat hypertension in hypertension-induced renal damage patients can reduce 24-hour urinary total protein (24 h UTP) [WMD = − 0.09, 95% CI(− 0.13, 0.05), 𝑃 = 0.001], but does not lower systolic blood pressure(SBP) [WMD = −1.02, 95% CI(−2.88, 0.84), 𝑃 = 0.281] or diastolic blood pressure(DBP) [WMD = −0.21, 95% CI(−1.71, 1.29), 𝑃 = 0.786] more effectively. There was also no statistically significant difference in adverse events between experimental groups and control groups. Conclusion: Breviscapine injection, in combination with antihypertensive drugs, appears to be more effective in improving the 24 h UTP, but overall have no effect on improving the blood pressure in hypertension-induced renal damage patients. Moderate dose of breviscapine injection(10ml) may have effects on reducing blood pressure in hypertension-induced renal damage patients but high doses of breviscapine injection(20ml) may increase blood pressure by subgroup analysis. However, the evidence of methodological quality and sample sizes is weak, and thus, further standardized research is required. Keywords: breviscapine injection, hypertension, systematic review, meta-analysis, effects